Self assembled CdLa2S4 hexagon flowers, nanoprisms and nanowires: novel photocatalysts for solar hydrogen production - Kale, Bharat B.; Baeg, Jin-Ook; Kong, Ki-jeong; Moon, Sang-Jin; Nikam, Latesh K.; Patil, Kashinath R. (Journal of Materials Chemistry, 2011)
We report here a new ternary chalcogenide material, cadmium lanthanum sulfide (CdLa2S4) produced using a facile hydrothermal method at 433 K. The effect of the solvent on the morphology of the CdLa2S4 was demonstrated for the first time. The prima facie observations revealed the formation of highly crystalline hexagonal structures in the form of flowers in aqueous medium. The flowers comprise hexagonal columns similar to 300 nm in diameter and 1-1.2 mu m in length. All the hexagonal structures have a sharp tip with a cavity of 10 nm and are almost equal in size. The nanoprisms have an average base size of 35 nm with 35 nm edges, and the nanowires have a diameter of 10-15 nm; both were obtained in methanol. Crystal and electronic structure calculations were performed using the Vienna ab initio simulation package (VASP) based on density functional theory (DFT). Considering the band gap of pristine CdLa2S4 in the visible region (2.3 eV), we have demonstrated CdLa2S4 as a photocatalyst for the production of H-2 under solar light. Nanostructured CdLa2S4 prisms gave the maximum hydrogen production, i.e. 2552 mu mol h(-1). Being a stable ternary nanostructured metal sulfide (with nanohexagons, nanoprisms, nanowires), CdLa2S4 may have other potential prospective applications in solar cells and optoelectronic devices.

Surfactant tunable hierarchical nanostructures of CdIn2S4 and their photohydrogen production under solar light - Bhirud, Ashwini P.; Chaudhari, Nilima; Nikam, Latesh; Sonawane, Ravindra; Patil, Kashinath; Baeg, Jin-Ook; Kale, Bharat (International Journal of Hydrogen Energy, 2011)
The hierarchical nanostructures of CdIn2S4 were selectively prepared through hydrothermal process in the presence of different surfactants. Structural study demonstrated existence of cubic spinel structure and micro structural study shown a pretty marigold flower like morphology without any surfactant. The effect of surfactants on the morphology and microstructure of CdIn2S4 has been studied by using Polyvinyl pyrrolidone (PVP) and Cetyltrimethyl ammonium bromide (CTAB) as a surfactants. The CdIn2S4 bipyramids with length of 0.7-1 mu m have been obtained using PVP. Interestingly, the nanopetals (thin and transparent) of CdIn2S4 are self assembled into hollow spheres in the presence of CTAB. Considering the importance of these unique nanostructures, the growth mechanism has also been proposed. The optical properties demonstrated the band gap in the range of 2.12-2.29 eV which is well within the visible region. In this contest, photocatalytic activity for hydrogen production using the above nanostructures under visible light was also demonstrated. The prima-fascia observations shows that the bipyramidal CdIn2S4 exhibit excellent photocatalytic activity for hydrogen production (3238 mu molh(-1)) than other nanostructures. Being a nanostructured semiconductor chalcogenide with a good stability will also have potential applications in solar cells and LED. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Bipyramids; CdIn2S4; Hydrogen generation; hydrothermal; Self-assembled

Situ fabrication of highly crystalline CdS decorated Bi2S3 nanowires (nano-heterostructure) for visible light photocatalyst application - Panmand, Rajendra P.; Sethi, Yogesh A.; Deokar, Rajashree S.; Late, Dattatray J.; Gholap, Haribhau M.; Baeg, Jin-Ook; Kale, Bharat B. (RSC Advances, 2016)
In situ synthesis of the orthorhombic Bi2S3 nanowires decorated with hexagonal CdS nanoparticles (nano-heterostructure) has been demonstrated by a facile solvothermal method. The tiny 5-7 nm CdS spherical nanoparticles are decorated on the surfaces of 30-40 nm Bi2S3 nanowires, successfully. Structural, morphological and optical studies clearly show the existence of CdS on the nanowires. A possible sequential deposition growth mechanism is proposed on the basis of experimental results to reveal the formation of the nano heterostructure. The heterostructures have been used as a photocatalyst for hydrogen production as well as degradation of methylene blue under solar light. The maximum hydrogen evolution i.e. 4560 and 2340 mu mol h(-1) 0.5 g was obtained from H2S splitting and glycerol degradation for Bi2S3 NWs decorated with CdS nanoparticles (nano-heterostructure) which is higher than that of the Bi2S3 NWs (3000 and 1170 mu mol h(-1) 0.5 g, respectively). The enhanced photocatalytical hydrogen evolution efficiency of the heterostructures is mainly attributed to its nanostructure. In the nano heterostructure, the CdS nanoparticles control the charge carrier transition, recombination, and separation, while the Bi2S3 nanowire serves as a support for the CdS nanoparticles. The photogenerated electron's migration is faster than the holes from the inside of a CdS nanoparticle to its surface or to the phase interface, resulting in a relatively higher hole density inside the CdS nanoparticle leaving electron density at surface of the Bi2S3 NWs. This influences the photocatalytic activity under solar light. Such nano-heterostructures may have potential in other photocatalytic reactions.